Reaksi Harga Saham di BEJ terhadap Pengumuman Pergantian Kepemimpinan Suharto - Nurhayatie, Tatiek; Mutamimah, Mutamimah; Slyamtinah, Slyamtinah (JURNAL BISNIS STRATEGI, 1999)
This research is meant to examine whether the investor earn abnormal return  with change Suharto leadership announcement or wether security prices reflect the information about change Suharto leadership announcement. In other worda, we can ask whether Jakarta Stock Excange is efficient in the category of semi strong form.  The samples in the research are 30 securities,  which chosen by using certain criteria.  The evaluation periode took place in  1998.For the research purpose, abnormal return test can be done. Abnormal return can be found by single index model.  The analysis result show that investor sill earn abnormal return with change  Suharto leadershlp announcement or security price  don't reflect the lnformaion abaout change Suharto leadership announcement.  This ls marked by average abnormal reurn which ls defferent from null (α =5%), change Suharto leadership announcement case. It means that Jakarta Sock Exchange isn't efficient in Semi strong form.